One new species of the genus Alloteratura Hebard, 1922 (Tettigoniidae: Meconematinae) and supplement of Alloteratura (Alloteratura) flabellata Xin & Shi, 2019 - Duan, Yueting; Wang, Yang; Cui, Peng; Chang, Yanlin (Zootaxa, 2024)
This paper describes one new species of the genus Alloteratura Hebard, 1922 from China, i.e. Alloteratura (Alloteratura) curvata sp. nov. In addition, supplementary description and morphological photographs of Alloteratura (Alloteratura) flabellata Xin & Shi, 2019 are provided and its intraspecific variation is discussed.